Transformasi Pondok Pesantren dalam Perspektif Kajian Literatur: Dinamika dan Inovasi Pendidikan Islam di Era Modern - Syakhrani, Abdul Wahab (PT. Sharia Journal and Education Center, 2025)
This research explores the transformation of Islamic boarding schools from a literature review perspective, focusing on the dynamics and innovations of Islamic education in the modern era. Pondok pesantren, which is one of the oldest Islamic educational institutions in Indonesia, has undergone significant changes to adapt to the demands of the times. This transformation includes a shift in curriculum from the traditional yellow book-based to a more inclusive and modern model, integration of technology in learning methods, as well as improved management and administration of the institution. In an effort to remain relevant, the pesantren have also strengthened cooperation with various educational institutions at home and abroad. The results of this study demonstrate that boarding schools not only successfully adapt to the changing times, but also play an important role in producing competitive and highly competitive graduates. In conclusion, the transformation that has occurred shows the ability of pesantren to remain an integral part of the national education system and contribute to the development of quality human resources. Keywords: Transformation, Islamic Boarding School, Literature Review.